Brandish Red Report Card: Eliminating Corruption in Indonesia - El-Adzkiyaa, Awhan Ibaad; Muttaqin, Labib; Adrian, Adrian (Interdisciplinary Social Studies, 2022)
Background: Provide an adequate background covering the literature review and the gap of the research with other relevant former research works. Aim: Mention the main purpose of the research. Method: Give a brief explanation regarding the method used, along with the sample, data collection technique, and data analysis technique. Findings: Summarize the collected data and the analysis performed on those data relevant to the issue that is to follow.